Impact of country-level corporate governance on entrepreneurial conditions - Faozi A. Al Maqtari; Najib H. S. Farhan; Hamood Mohd. Al-Hattami; Amgad S. D. Khalid (Cogent Business & Management, 2020)
The present study examines the effect of country-level corporate governance (CLCG) and Directors' Liability (DL) on Entrepreneurial Framework Conditions (EFCs) across 52 countries from 2014 up to 2017 using balanced panel data and Panel Correction Standard Error estimation. The results revealed that the CLCG has a significant impact across EFCs dimensions. Further, the results declared that the impact of DL is significant and positive in countries that have a high score of DL, but this impact is statistically negative in countries that have a low score of DL. The findings have momentous implications for entrepreneurs, policymakers, regulators, international organizations, and academicians. The study makes novel contributions to the strand literature underpinning country-level governance and the role of directors' liability with EFCs. It brings a useful insight into a previously undocumented area of research highlighting the importance of CLCG dimensions and DL as important factors and determinants for better entrepreneurial conditions.
Keywords: 650; country-level corporate governance; entrepreneurship; entrepreneurial conditions; entrepreneurial framework; panel correction standard error